2016
DOI: 10.1093/mnras/stw852
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and kinematics of the Hercules stream

Abstract: An abundance analysis is reported of 58 K giants identified by Famaey et al. (2005) as highly probable members of the Hercules stream selected from stars north of the celestial equator in the Hipparcos catalogue.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The Hercules stream is almost missing in the TD map, so that probably is constructed mostly of thin disk stars. The same result was obtained by Bensby et al (2014) and Ramya et al (2016) from a chemical abundances analysis of stars that belong to the Hercules (for more discussions see Sect. 5.4).…”
Section: Thin and Thick Disk Structuressupporting
confidence: 81%
See 1 more Smart Citation
“…The Hercules stream is almost missing in the TD map, so that probably is constructed mostly of thin disk stars. The same result was obtained by Bensby et al (2014) and Ramya et al (2016) from a chemical abundances analysis of stars that belong to the Hercules (for more discussions see Sect. 5.4).…”
Section: Thin and Thick Disk Structuressupporting
confidence: 81%
“…Later, Bensby et al (2014) re-examined the chemical composition of Hercules stream stars and found that it mainly consists of stars that chemically can be associated with both the thin and thick disks. Ramya et al (2016) on the other hand studied 58 Hercules stream red giants and found that they are mostly metalrich stars from the thin disk. The somewhat discrepant results could be explained with different target selection methods used by the two studies.…”
Section: Individual Structuresmentioning
confidence: 99%
“…), to explore the mysterious "cosmological lithium problem" (Fu et al 2015), to derive the main parameters of star clusters (for instance, Donati et al 2014;Borissova et al 2014; San Roman et al 2015; Goudfrooij et al 2015) and Galactic structure (e.g. Küpper et al 2015;Li et al 2016;Balbinot et al 2016; Ramya et al 2016), to study dust formation (e.g. Nanni et al 2013;Nanni et al 2014), to constrain dust extinction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It must be remembered that the figure represents the arms in their own standard of rest, which rotates with a velocity of the order of 28 km/s/kpc, in the inertial frame. Ramya et al (2016) performed a detailed study of the stellar population of the Hercules stream. They found an average metallicity of the order of (Fe/H) 0.15, Ziurys (2006), Glassgold (1996), Agúndez et al (2014), the 2018 Census of molecular detections presented by McGuire (2018), and current detections reported by Cernicharo et al (2019).…”
Section: Dynamics Very Close To the Sun Moving Groups And Stellar Streamsmentioning
confidence: 99%